Social engagement, self‐efficacy, and posttraumatic stress symptoms across 6 months of psychotherapy. Issue 1 (6th August 2020) - Shoji, Kotaro; Smith, Andrew J.; Sano, Riko; Samuelson, Kristin W.; Benight, Charles C.
Abstract: Objective: The current study was conducted in a naturalistic treatment setting to examine whether and how perceptions about social engagement, trauma coping self‐efficacy, and posttraumatic stress symptoms (PTS) influence one another across 6 months of psychotherapy for trauma survivors. Method: The sample included 183 clients who reported exposure to traumatic events and significant PTS (PCL‐5 ≥ 33). Participants ( M age  = 37.8, 53.6% female) completed surveys at intake, 3 months, and 6 months into treatment. A cross‐lagged panel analysis was used to test the relationships among perceived social engagement, coping self‐efficacy, and PTS across three assessment points. Results: PTS at 3‐months was a mediator in the relationship between intake perceived social engagement and 6‐month coping self‐efficacy and between intake perceived social engagement and 6‐month perceived social engagement. Conclusions: PTS several months into treatment may serve as a mechanism between intake perceived social engagement and functional outcomes such as coping self‐efficacy.